2020
DOI: 10.3390/s20154148
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Numerical Investigation to Characterize an Aerospace Composite Material with Open-Hole Using Non-Destructive Techniques

Abstract: In this study, the open-hole quasi-static tensile and fatigue loading behavior of a multidirectional CFRP thick laminate, representative of laminates used in the aerospace industry, is studied. Non-destructive techniques such as infrared thermographic (IRT) and digital image correlation (DIC) are used to analyze the behavior of this material. We aim at characterizing the influence of the manufacturing defects and the stress concentrator through the temperature variation and strain distribution during fatigue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Even though not explicated, a damage index for optical methods can be written as: where and are the deformations in the undamaged and damaged state, with i and j the directions of measurement. The DIC is among the most promising techniques for the nondestructive characterization of composites [ 72 , 73 ]. In the literature, its application at the microscale of carbon fiber composites has been also investigated [ 74 ].…”
Section: Optical Methodsmentioning
confidence: 99%
“…Even though not explicated, a damage index for optical methods can be written as: where and are the deformations in the undamaged and damaged state, with i and j the directions of measurement. The DIC is among the most promising techniques for the nondestructive characterization of composites [ 72 , 73 ]. In the literature, its application at the microscale of carbon fiber composites has been also investigated [ 74 ].…”
Section: Optical Methodsmentioning
confidence: 99%
“…Moreover, its accuracy is inevitably affected by uncontrollable energy dissipation [ (8)(9)(10)]. DIC, an optical based image stress analysis method, has been used combining with IRT to study thermomechanical coupling effects [ (11)(12)(13)]. Nonetheless, there are seldom researches have been done about applying this synchronous detecting system in SIF detection, which requires high accuracy of point stress state measurement.…”
Section: Introductionmentioning
confidence: 99%
“…It is of great significance to accurately predict the failure mode and strength of CFRP composites with open hole. Feito et al 13 investigated the tensile and fatigue properties of open‐hole carbon fiber composites by using digital image correlation method and infrared thermographic. Results showed that the increase of inter‐laminar temperature can be significantly reduced with the change of fiber orientation in loading direction.…”
Section: Introductionmentioning
confidence: 99%